SerpinB3 as a Pro-Inflammatory Mediator in the Progression of Experimental Non-Alcoholic Fatty Liver Disease - Novo, Erica; Cappon, Andrea; Villano, Gianmarco; Quarta, Santina; Cannito, Stefania; Bocca, Claudia; Turato, Cristian; Guido, Maria; Maggiora, Marina; Protopapa, Francesca; Sutti, Salvatore; Provera, Alessia; et al. (Frontiers in Immunology, 2022)
Non-alcoholic fatty liver disease (NAFLD) is becoming the most common chronic liver disease worldwide. In 20-30% of patients, NAFLD can progress into non-alcoholic steatohepatitis (NASH), eventually leading to fibrosis, cirrhosis and hepatocellular carcinoma development. SerpinB3 (SB3), a hypoxia-inducible factor-2α dependent cysteine protease inhibitor, is up-regulated in hepatocytes during progressive NAFLD and proposed to contribute to disease progression. In this study we investigated the pro-inflammatory role of SB3 by employing phorbol-myristate acetate-differentiated human THP-1 macrophages exposed in vitro to human recombinant SB3 (hrSB3) along with mice overexpressing SB3 in hepatocytes (TG/SB3) or knockout for SB3 (KO/SB3) in which NASH was induced by feeding methionine/choline deficient (MCD) or a choline-deficient, L-amino acid defined (CDAA) diets. In vivo experiments showed that the induction of NASH in TG/SB3 mice was characterized by an impressive increase of liver infiltrating macrophages that formed crown-like aggregates and by an up-regulation of hepatic transcript levels of pro-inflammatory cytokines. All these parameters and the extent of liver damage were significantly blunted in KO/SB3 mice. In vitro experiments confirmed that hrSB3 stimulated macrophage production of M1-cytokines such as TNFα and IL-1β and reactive oxygen species along with that of TGFβ and VEGF through the activation of the NF-kB transcription factor. The opposite changes in liver macrophage activation observed in TG/SB3 or KO/SB3 mice with NASH were associated with a parallel modulation in the expression of triggering receptor expressed on myeloid cells-2 (TREM2), CD9 and galectin-3 markers, recently detected in NASH-associated macrophages. From these results we propose that SB3, produced by activated/injured hepatocytes, may operate as a pro-inflammatory mediator in NASH contributing to the disease progression.